2020
DOI: 10.1186/s12891-020-03327-w
|View full text |Cite
|
Sign up to set email alerts
|

Work- and stress-related musculoskeletal and sleep disorders among health professionals: a cross-sectional study in a hospital setting in Switzerland

Abstract: Background: Musculoskeletal and sleep disorders have been reported to be very common among health care and hospital workers and particularly nurses. They are assumed or found to be a result of psychological stress and/or physical strain or pain. However, no other study so farat least in a hospital setting and for Switzerlandhas considered and investigated musculoskeletal as well as sleep disorders in consequence of or rather in association with both physical workload and psychological stress. Methods: Cross-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
54
1
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 33 publications
3
54
1
9
Order By: Relevance
“…Results with a similar magnitude of excess risks of sickness absence were found for the combinations of job control and heavy physical work and strenuous postures, respectively. These results are in-line with research reviews and previous studies on how combinations of physical and psychosocial exposures among health and social care workers affect health, sickness absence, or disability [ 24 , 26 , 27 , 29 , 30 , 31 , 32 , 33 , 49 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Results with a similar magnitude of excess risks of sickness absence were found for the combinations of job control and heavy physical work and strenuous postures, respectively. These results are in-line with research reviews and previous studies on how combinations of physical and psychosocial exposures among health and social care workers affect health, sickness absence, or disability [ 24 , 26 , 27 , 29 , 30 , 31 , 32 , 33 , 49 ].…”
Section: Discussionsupporting
confidence: 90%
“…The fact that there were fewer nurses than care assistants in the study affected the statistical measurements, and the large confidence intervals also indicated heterogeneity among the employees of both groups. As shown in recent research, the working conditions among nurses, as well as among care assistants, are diverse with respect to work obligations and work organizations [ 24 , 25 , 26 , 27 , 28 , 30 , 31 , 32 , 33 , 34 , 36 ]. Some nurses and care assistants who reported both harmful psychosocial and physical challenges may be able to handle their activities in a planned way, while other employees have to work in urgent situations more regularly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nurses responded to questionnaires with items on lifestyle, health, and working environment, and the study findings indicated that moderate and high stress at baseline increased the odds of LBP at one year follow up with odds ratios (OR) of 1.39 (95% CI 1.13-1.71) and 1.99 (95% CI 1.49-2.66) respectively. The researchers concluded that psychological stress increases the odds of LBP among healthcare workers, and similar findings were found in the cross-sectional study done by Hammig (2020) 63,65. Al-Hadidi et al (2020) carried out a cross-sectional study on the prevalence of LBP among female Jordanian Hospital staff at childbearing age since low back…”
mentioning
confidence: 59%
“…61 More so, research in occupational medicine has identified several physical and psychological risk factors for the development of WMSD. Also, previous studies have shown that MSD was63 Schroder and Nienhous (2020) conducted a systematic review and meta-analysis to examine the occurrence of Work-related intervertebral disc disease of the lumbar spine (LDD) among health personnel. Five studies reported a high prevalence of LDD among nurses and geriatric nurses (11.3% -96.3%) compared to all controls (3.8% -76.5%).…”
mentioning
confidence: 99%